Analisis Struktur dan Kesalahan Kebahasaan pada Beberapa Laporan Penelitian Mahasiswa (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This research aims to analyze the structure and identify various forms of linguistic errors found in students’ research reports. A qualitative approach with a descriptive method was employed, using documentation studies on three different students’ research reports as the primary data. The findings indicate discrepancies in the text structure, such as unsystematic composition of the introduction, methodology, results, discussion, and conclusion sections. Furthermore, various linguistic errors were identified, including spelling, punctuation, diction, ineffective sentence construction, and inconsistencies in citations and references. Other identified issues include content duplication, technical errors in word processing features, and lack of relevance in the theoretical review. The implications of this research emphasize the necessity of improving the quality of research report writing through strengthened academic writing curricula, structured mentoring, the use of reference management technology, and a disciplined scientific literacy culture. This study is expected to serve as an evaluation tool for students, lecturers, and study programs to enhance the standards of scientific writing in higher education.